2023
DOI: 10.1128/jmbe.00153-23
|View full text |Cite
|
Sign up to set email alerts
|

Chatbot responses suggest that hypothetical biology questions are harder than realistic ones

Gregory J. Crowther,
Usha Sankar,
Leena S. Knight
et al.

Abstract: The biology education literature includes compelling assertions that unfamiliar problems are especially useful for revealing students’ true understanding of biology. However, there is only limited evidence that such novel problems have different cognitive requirements than more familiar problems. Here, we sought additional evidence by using chatbots based on large language models as models of biology students. For human physiology and cell biology, we developed sets of realistic and hypothetical problems match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…Insights into this dynamic are provided by a study evaluating ChatGPT models' advanced cognitive abilities in biology, utilizing both standard and hypothetical questions. The study found that ChatGPT models performed notably poorer on questions involving concepts of redefinition or invention [27]. Emerging evidence suggests that AI may exhibit its own cognitive process, as indirectly indicated by a trend of improved performance on questions at the lower levels of Bloom's taxonomy, particularly in disciplines such as neurology, radiology, physiology, microbiology, and biochemistry [28][29][30][31][32].…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…Insights into this dynamic are provided by a study evaluating ChatGPT models' advanced cognitive abilities in biology, utilizing both standard and hypothetical questions. The study found that ChatGPT models performed notably poorer on questions involving concepts of redefinition or invention [27]. Emerging evidence suggests that AI may exhibit its own cognitive process, as indirectly indicated by a trend of improved performance on questions at the lower levels of Bloom's taxonomy, particularly in disciplines such as neurology, radiology, physiology, microbiology, and biochemistry [28][29][30][31][32].…”
Section: Comparison With Prior Workmentioning
confidence: 99%